MENATA KEMBALI DESENTRALISASI INDONESIA DALAM BINGKAI NEGARA KESATUAN REPUBLIK INDONESIA - Warkhatun Najidah (Law Department, University of Widya Gama Mahakam Samarinda, 2010)
Local Authonomy in Negara Kesatuan Republik Indonesia are different with aouthonomy on federal state. Desentralisation implementation must be evaluated. Local Authonomy with regulation on UU 22/1999 and UU 32/ 2004 have different paradigm about local otonomy.But uniformities always happen ini all local authonomy history. Desentralisation are instrument for authonomy will be change but state have task to reconstruction all aspect about that. Asymerical Desentralisation are the answer for Indonesian government because this is will be accommodate pluralism condition and cultur in Indonesia.